Wacana Trauma dalam Haiku Pascaperang Dunia II: Kajian Semiotika Budaya Lotman - Ni Luh Gede Meilantari; Ni Putu Dini Febriyanti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the utilization of haiku as a form of response to postwar trauma through Kaneko Tota’s and Saito Sanki’s war-themed haiku. Following Japan’s defeat in World War II in 1945, a cultural shift occurred marked by transformation within traditional arts, particularly haiku, which became a significant medium for expressing traumatic historical and social experiences. Although both poets used haiku as a medium to express dissatisfaction and critique the socio-political conditions of the postwar period, they represented different generations and approaches in responding to postwar trauma. Saito, having directly experienced the trauma of war, developed a deconstructive strategy towards traditional haiku conventions. Meanwhile, Kaneko, belonging to the postwar generation, adopted a more radical approach in formal and semantic experimentation. These dual strategies not only embodied individual artistic responses to trauma but also contributed to a broader cultural project aimed at reconstructing Japan’s collective identity in the postwar era. Yuri Lotman’s cultural semiotics framework is employed to analyze the semiotic transformation dynamics in the poets' works. Lotman’s theory, with its key concepts of semiosphere, cultural text, and translation mechanisms, offers a comprehensive analytical tool for understanding the dynamics of sign systems and cultural meanings in World War II-themed haiku. From the analysis of five war-themed haiku, it is concluded that both poets constructed a collective trauma discourse. Rather than employing explicit descriptive narratives, the trauma discourse utilizes strong semiotic condensation strategies. Saito and Kaneko juxtaposed established cultural symbols and codes, such as Hiroshima as a metaphor of absolute destruction, the marathon as a symbol of life, breasts as a symbol of motherhood, and blooming flowers representing renewal into new surreal configurations that created novel meanings at the semiotic boundaries where tensions clashed.